Patterns of emergency department utilization between transplant and non‐transplant centers and impact on clinical outcomes in kidney recipients. Issue 9 (8th July 2020) - Perkins, Haley; Taber, David; Patel, Neha; Rohan, Vinayak; Su, Zemin; Dubay, Derek; McGillicuddy, John
Abstract: There is a high rate of Emergency Department (ED) utilization in kidney recipients post‐transplant; ED visits are associated with readmission rates and lower survival rates. However, utilization within and outside transplant centers may lead to different outcomes. The objective was to analyze ED utilization patterns at transplant and non‐transplant centers as well as common etiologies of ED visits and correlation with hospitalization, graft, and patient outcomes. This was a longitudinal, retrospective, single‐center cohort study in kidney transplant recipients evaluating ED utilization. Comparator groups were determined by ED location, time from transplant, and disposition/readmission from ED visit. 1, 106 kidney recipients were included in the study. ED utilization dropped at the transplant center after the 1st year ( P < .001), while remaining at a similar rate at non‐transplant centers (0.22 vs 1.06 VPPY). Infection and allograft complications were the most common causes of ED visits. In multivariable Cox modeling, an ED visit due to allograft complication at a non‐transplant center >1 year post‐transplant was associated with higher risk for graft loss and death (aHR 2.93 and aHR 1.75, P < .0001). The results of this study demonstrate an increased risk of graft loss among patients who utilize non‐transplant center emergency departments. Improved communication and coordination between transplant centers and non‐transplant centers may contribute to better long‐term outcomes.